A dynamic factor analysis of business cycle on firm-level data - Lucia Alessi; Matteo Barigozzi; Marco Capasso (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
We use the Generalized Dynamic Factor Model proposed by Forni et al. [2000] in order to study the dynamics of the rate of growth of output and investment and establish stylized facts of business cycles. By using quarterly firm level data relative to 660 US firms for 20 years, we investigate the number and the features of the underlying forces leading economic growth: evidence suggests the main shock to be the same across sectors and for the economy as a whole. Moreover, we disentangle the component of industrial dynamics which is due to economy-wide factors, the common component, from the component which relates to sectoral or firm-specific phenomena, the idiosyncratic component. We assess the relative importance of these two components at different frequencies and compare common components across sectors. Finally, we investigate the comovements of the common component of output and investment series both at firm level and at sectoral level.
Keywords: C51; E32; O30; 330; Dynamic Factor Analysis; Business Cycle; Comovements; Konjunktur; Unternehmenswachstum; USA